PERSEPSI PENGEMBANGAN KARIR DITINJAU DARI KONFLIK PERAN GANDA DAN DUKUNGAN SOSIAL PADA KARYAWAN WANITA DI PT. GULA PUTIH MATARAM LAMPUNG TENGAH - Viranda Rinantri; Alimatus Sahrah (Jurnal Penelitian Humaniora, 2014)
he aim of this research was to examine the relation between doable role con lict and social support toward women who work in carrier development perception. The subject of this research was 62 women who work in human resource at PT.Gula Putih Mataram, Central Lampung who had minimum a year experience. Data were collected by using carrier development perception scale, double role con lict scale and social support scale. Here the data was analyzed with double regretion. The result showed that the biggest affed of this analysis were social support with beta value 0,473, instead of double role con lictbeta value -0,335 in short, double role con lict gave 10,4 % affection for carrier development perception and 23,4 % in social support